Challenges of the reform of the position of juvenile victims of crime in the Republic of Serbia - Mirić Filip (Temida, 2016)
The paper offers an analysis of the possible directions of the reform of juvenile criminal legislation with regard to the position of juvenile victims of crime in Serbia. The paper analyses provisions of national and international legal acts, relevant and important for the legal protection of juvenile victims. The aim is to point out the challenges and problems in the process of reform of juvenile law, which are directed towards building a “child-friendly justice” system. In this way, as the author points, it is possible to get valuable information on which direction the reform of juvenile criminal legislation should go in order to provide basis for prevention of secondary victimization of juvenile victims of crime in the criminal procedure.